2016
DOI: 10.1007/s00431-016-2742-6
|View full text |Cite
|
Sign up to set email alerts
|

Congenital diaphragmatic hernia—influence of fetoscopic tracheal occlusion on outcomes and predictors of survival

Abstract: • Randomised controlled trials have demonstrated that foetal endotracheal occlusion (FETO) in high risk infants with congenital diaphragmatic hernia is associated with a higher survival rate. • Mortality is greater in foetuses who underwent FETO and delivered prior to 35 weeks of gestation. What is New: • Infants who had undergone FETO compared to those who had not had significantly longer durations of mechanical ventilation, supplementary oxygen and hospital stay. • Regardless of antenatal intervention, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…King's College Hospital NHS Foundation Trust is a referral centre for fetal tracheal occlusion (FETO) and approximately one-third of the population studied had FETO. Those infants were born at an earlier gestational age (data not shown), as we have previously demonstrated 14. There was, however, no significant difference in the proportions of infants who had undergone FETO and who did and did not survive (table 1), which may reflect improvements in the lung-to-head ratio following FETO.…”
Section: Discussionsupporting
confidence: 55%
“…King's College Hospital NHS Foundation Trust is a referral centre for fetal tracheal occlusion (FETO) and approximately one-third of the population studied had FETO. Those infants were born at an earlier gestational age (data not shown), as we have previously demonstrated 14. There was, however, no significant difference in the proportions of infants who had undergone FETO and who did and did not survive (table 1), which may reflect improvements in the lung-to-head ratio following FETO.…”
Section: Discussionsupporting
confidence: 55%
“…Previous research has shown that tracheal occlusion can indeed cause an increase in lung growth [51,52] and removing the balloon before birth has shown to be necessary for a better maturation of the lung by decreasing the apoptosis of the alveolar type 2 cells, which produce surfactant, an essential compound for lung function [53]. So far, FETO has been shown to improve survival rate in high-risk CDH patients, but at the cost of increased morbidity and premature delivery [54][55][56]. The results of the TOTAL trial will hopefully provide a more definitive answer.…”
Section: Treatment Of Pulmonary Vascular Defects In Cdhmentioning
confidence: 99%
“…Conversely, artificially increasing luminal pressures has shown to rescue lung hypoplasia in animal models. These results have been used clinically to develop a procedure called fetal endoscopic tracheal occlusion (FETO) [78]. FETO uses a small balloon inflated within the intubated fetal trachea to block fluid efflux out of the lung and increase the fluid pressure within the developing lung.…”
Section: Examples Of Fluid Mechanical Regulation Of Organogenesismentioning
confidence: 99%
“…FETO uses a small balloon inflated within the intubated fetal trachea to block fluid efflux out of the lung and increase the fluid pressure within the developing lung. FETO and strategies used to increase transepithelial Cl− flux have been attempted in utero to increase the lumenal fluid pressure with modest success to date in humans [7880]. As such, it is clear that the in utero mechanical environment is complex and additional study is needed to understand how pressure and/or local dynamic pressures and flows from peristaltic smooth muscle contractions spatially induce cellular mechanotransduction pathways that regulate lung morphogenesis.…”
Section: Examples Of Fluid Mechanical Regulation Of Organogenesismentioning
confidence: 99%